Zombie banks how broken banks and debtor nations are crippling the global economy - Onaran, Yalman, 1969-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2012)
"An in-depth look at the essential issues surrounding zombie institutions and their effect on the global economyZombie banking has become standard operating procedure for big debtor nations. They prop up failing institutions, print money, and avoid financial corrections. But in an attempt to prolong the inevitable, bigger problems are created. The approach used now has not, and will not, work. This timely book reveals why. Zombie Banking tells the story of how debtor nations and failing institutions are damaging the long-term prospects of the global economy. Author Yalman Onaran, a veteran Bloomberg News reporter and financial banking sector expert, examines exactly what a zombie bank is and why they are kept alive. He also discusses how they hurt economic recovery and what needs to be done in order to restore stability. Along the way, Onaran takes an honest look at how we arrived at this point and details the harsh realities that must be faced, and the serious steps that must be taken, in order to get things headed in the right direction. Puts insolvent banks and debtor nations in the spotlight and examines how they are crippling the global economy On the record sources include Paul Volcker, Joseph Stiglitz, Sheila Bair, and many more bank executives, regulators, politicians, and policymakers in the United States and abroad Takes the complexity of the current situation and translates it in a way that makes it understandable While the short-term measures taken to stave off depression and rejuvenate economic growth may offer hope, they are unsustainable over the long term. Get a better look at what really lies ahead, and what it will take to improve our economic situation, with this book"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Debts, External -- History -- 21st century; Banks and banking -- History -- 21st century; Economic history -- 21st century; Electronic books